Probiotics: Properties, Examples, and Specific Applications - Behnsen, Judith (Cold Spring Harbor Laboratory Press, 2013)
Probiotics are beneficial components of the microbiota that have been used for centuries because of the health benefits they confer to the host. Only recently, however, has the contribution of probiotics to modulation of immunological, respiratory, and gastrointestinal functions started to be fully appreciated and scientifically evaluated. Probiotics such as Escherichia coli Nissle 1917 and lactic acid bacteria are currently used to, or have been evaluated for use to, prevent or treat a range of intestinal maladies including inflammatory bowel disease, constipation, and colon cancer. Engineering these natural probiotics to produce immunomodulatory molecules may help to further increase the benefit to the host. In this article, we will discuss some of the mechanisms of action of probiotics as well as advances in the rational design of probiotics.